Evaluation of Land Suitability for Shrimp Ponds in Alue Naga village, Syiah Kuala sub-district - Afriyani, Mice Putri; Muttakin, Muttakin; Nurfachdini, Nurfachdini (Jurnal Wilayah dan Lingkungan, 2024)
Alue Naga Village is located in the coastal area of the Syiah Kuala sub-district, which has the potential for shrimp pond cultivation. A mistake in choosing a pond location will cause problems, one of which is environmental. The purpose of this study was to determine the suitability of land for shrimp pond cultivation in Alue Naga village. The samples tested directly in this study measured the level of salinity and soil pH at predetermined pond points and were marked using the Avenza Maps application based on a simple random sampling technique. This research uses overlay and scoring method analysis. The parameters used and analyzed were: land use, soil texture, soil type, soil pH, land slope, distance from the river, distance from the coastline, and salinity. The results of the spatial analysis show three classifications of land classes for shrimp pond cultivation, namely: 1) The class is very suitable for pond cultivation (S1), with an area of 85.15 ha and a percentage of 59.72%. 2) Class suitable for pond cultivation (S2), with an area of 56.91 ha and a percentage of 39.91% 3) Conditionally suitable class for pond cultivation (S3), with an area of 0.52 ha and a percentage of 0.36% There are no ponds in unsuitable areas. The dominant factor affecting the development of ponds in Alue Naga village is land use, most of which is already in the area where they should be, and the salt content is in accordance with the criteria.